Is there really a pot of gold at the end of the rainbow? Has the Occupational Specific Dispensation, as a mechanism to attract and retain health workers in South Africa, leveled the playing field? - George Gavin; Rhodes Bruce (BMC, 2012)
Abstract Background South Africa is experiencing a critical shortage of human resources for health (HRH) at a time when the population and the burden of ill-health, primarily due to HIV, AIDS and TB, are on the increase. This shortage is particularly severe within the nursing profession, which has witnessed significant emigration due to poor domestic working conditions and remuneration. Salaries and other benefits are an obvious pull factor towards foreign countries, given the often extreme international wage differentials. The introduction of the Occupation Specific Dispensation (OSD) in 2007 sought to improve the public services' ability to attract and retain employees thereby reducing incentives to emigrate. Methods Using a representative basket of commonly bought goods (including food, entertainment, fuel and utilities), a purchasing power parity (PPP) ratio is an exchange rate between two currencies that equalises the international price of buying that basket. Our study makes comparisons, using such a PPP index, and allows the identification of real differences in salaries for our selected countries (South Africa, United States, United Kingdom, Canada, Australia and Saudi Arabia) for the same HRH professions. If PPP adjusted earnings are indeed different then this indicates an economic incentive to emigrate. Results Salaries of most South African HRH, particularly registered nurses, are dwarfed by their international counterparts (notably United States, Canada and Saudi Arabia), although the OSD has gone some way to reduce that disparity. All selected foreign countries generally offer higher salaries on a PPP adjusted basis. The United Kingdom ($43202) and Australia ($38622), in the category of Medical Officer, are the only two examples where the PPP adjustment brings the salary below what is being offered in South Africa ($50013 post OSD). The PPP adjusted salary differences between registered nurses is very slight for South Africa ($18884 post OSD), Australia ($21784) and the United Kingdom ($20487). All other foreign countries show large salary advantages across the HRH categories examined. Conclusion Whilst South African salaries remain lower than their foreign counterparts by and large, the introduction and implementation of the OSD has made significant progress in reducing the gap between salaries of HRH in South Africa (SA) and the rest of the world. Given that the OSD has narrowed the gap between SA and overseas salaries whilst in the context of continued out migration of SA HRH, further research into push factors effecting migration needs to be undertaken.